2006
DOI: 10.1002/adem.200600046
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Homogenization Strategies in Material Modeling of Thermally Sprayed TBCs

Abstract: Partially yttria stabilized zirconia (PYSZ) thermal barrier coatings (TBCs) are applied in aircraft engines and gas turbines. Especially PYSZ coatings on turbine blades fulfill a heat and corrosion functionality during the operational use of the gas turbines. The PYSZ-layers lead to an increase of the life time of the turbine blades due to a decrease of the thermal and mechanical loading of the Ni-alloy components during gas turbine operation. For this reason, PYSZ-TBCs can also limit the costs of the turbine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This model has shown the influence of substrate surface on deformation and solidification of the particle and it was found that the substrate surface can also significantly influence on the deposition efficiency. This model will be further developed for a successive particle impact and overlaying to simulate the evolution of microstructure built during atmospheric plasma spray processes which will be used to calculate effective mechanical and thermal properties by homogenisation methods [16].…”
Section: Discussionmentioning
confidence: 99%
“…This model has shown the influence of substrate surface on deformation and solidification of the particle and it was found that the substrate surface can also significantly influence on the deposition efficiency. This model will be further developed for a successive particle impact and overlaying to simulate the evolution of microstructure built during atmospheric plasma spray processes which will be used to calculate effective mechanical and thermal properties by homogenisation methods [16].…”
Section: Discussionmentioning
confidence: 99%
“…This result arises because the columnar structure and the pore-crack architecture of in situ remelted coatings improve the compliance and decrease the permeability of TBCs; hence reducing the TGO formation. [20] Moreover, as-sprayed and in situ remelted coatings present the same resistance of about 75±80 cycles to thermal shock tests. It could be that this test is too severe as a means to differentiate these coatings.…”
mentioning
confidence: 90%
“…Descriptions of the methods as well as consideration of the peculiarities of their application to coating structures can be found in Refs. [33][34][35][36][37][38][39][40][41][42] Here, temperature dependency of effective Young's modulus was investigated with use of the homogenization for periodic structures. This method, described firstly in Ref., [41,42] needs properties of the microstructure components (ceramics and ''voids'' in our case) together with the representative volume element (RVE) of the microstructure as input.…”
Section: Coating Properties Simulationmentioning
confidence: 99%